Molecular phylogenetic relationships based on chloroplast genomes of Zingiberaceae species: Insights into evolution and adaptation to extreme environments - Lu, Tian; Yin, Yebing; Luo, Jinglin; Chen, Jiao; Wu, Yu; Zhang, Wu; Wei, Yiling; Yuan, Tao (Frontiers in Plant Science, 2025)
IntroductionThe Zingiberaceae family, which includes numerous economically and medicinally important species, exhibits considerable phylogenetic and genetic diversity. Chloroplast genomes are valuable resources for studying evolutionary relationships, genetic diversity, and adaptive evolution in plants. While many Zingiberaceae chloroplast genomes have been sequenced, the evolutionary mechanisms—including structural variation, codon usage bias, selection pressures, and divergence history—remain to be comprehensively investigated. Methodswe performed a comparative analysis of 11 newly identified species (Aframomum alboviolaceum, Amomum longipetiolatum, Amomum petaloideum, Amomum velutinum, Cautleya spicata, Cornukaempferia larsenii, Globba atrosanguinea, Globba variabilis, Hedychium aureum, Riedelia arfakensis, and Zingiber citriodorum) and 110 published data from the Zingiberaceae family, including their structure, codon usage, nucleotide polymorphisms, divergence time, and selection pressures.ResultsThe chloroplast genomes of Zingiberaceae species exhibited a highly conserved structure with no significant expansion or contraction during diversification. Analysis revealed four hypervariable protein-coding genes (atpH, rpl32, ndhA, and ycf1) and one intergenic region (psac-ndhE), which are proposed as potential molecular markers for future phylogeographic and population genetic studies. Codon usage bias was found to be predominantly shaped by natural selection. Phylogenetic analysis strongly supported the division of Zingiberaceae into two primary subfamilies (Alpinioideae and Zingiberoideae) and clarified key relationships, revealing that Globba is more closely related to Curcuma than to Hedychium, and Hedychium is more closely related to the Pommereschea-Rhynchanthus clade than to Cautleya. Divergence time estimation indicated two rapid diversification events within Zingiberoideae, coinciding with the rapid uplift of the Tibetan Plateau and a Late Miocene cooling event linked to declining CO₂ levels. Ancestral range reconstruction suggested an African origin during the Cretaceous period, followed by dispersal to Southeast Asia and India. Selection pressure analysis showed that most protein-coding genes are under negative selection. In contrast, the ycf2 gene was found to be under relaxed selection. Furthermore, two genes (matK and ndhB) were identified to be under positive selection in high-altitude species of Roscoea, suggesting a role in adaptation to alpine environments.DiscussionThis study provides a comprehensive genomic analysis of the Zingiberaceae family, highlighting the conserved nature of chloroplast genome structure despite extensive diversification. The identified mutation hotspots present valuable tools for developing high-resolution markers for species identification and biogeographic studies. The phylogenetic results resolve longstanding uncertainties in the relationships among key genera. The inferred divergence times and ancestral range suggest that the evolutionary history of Zingiberaceae was significantly influenced by major geological and climatic events, notably the uplift of the Tibetan Plateau and global cooling in the Late Miocene. The prevalence of negative/purifying selection across most genes indicates strong evolutionary constraints to maintain core photosynthetic functions. The discovery of positively selected genes in high-altitude Roscoea species provides insights into adaptive evolution to environmental stressors. These findings offer foundational knowledge for future efforts in crop improvement, species identification, and the conservation of genetic diversity within the Zingiberaceae family.